THE SYSTEMATIC LITERATURE REVIEW OF THE IMPACT OF FINTECH IN ENCOURAGING GREEN INNOVATION IN MSMEs - Sinaga, Royanti; Yunanda, Fayeno (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study investigates the role of fintech in promoting green innovation among Small and Medium Enterprises (SMEs) worldwide. This paper analyses various research studies and highlights key aspects of fintech’s contributing to sustainable business practices. Firstly, fintech supports access to finance through digital platforms and innovative financing models such as peer-to-peer lending (P2P), enabling SMEs to invest in environmentally friendly technologies. Secondly, green financing mechanisms such as crowdfunding and blockchain technology facilitate transparent and accountable investments in sustainable projects. Thirdly, fintech promotes the digitalization of business operation processes, increasing efficiency and reducing carbon footprints. Furthermore, fintech contributes to developing financial literacy, empowering SMEs to make better decisions about sustainable investments. The study also explores how fintech incentives, such as rewards for eco-friendly purchases, could drive consumer demand for sustainable products. To sum up, fintech plays a vital role in fostering green innovation among SMEs by providing better access to finance, promoting transparency, introducing eco-friendly technologies, and expanding market access. Keywords: Fintech; Green Innovation; MSMEs